Pelatihan dan Pendampingan Pelaksanaan Layanan Bimbingan dan Konseling - Andi Bunyamin; M Zain Irwanto; Muhammad Syahrul (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The aims of this activity was to increase the understanding and skills of BK teachers at MA DDI Wal Irsyad, in designing and implementing guidance and counseling services in schools. The methods used are 1) Participants are provided with an understanding of the theories related to counseling and aspects being trained. Furthermore, guidance and counseling teachers are given assistance in designing the implementation of guidance and counseling services in schools, 2) After the training and mentoring activities are completed, the results are presented in the seminars, 3) at the final stage of program implementation in schools, monitoring and observation are also carried out for analysis as far as where the effectiveness of guidance services for students, this is done in the form of interviews with teacher representatives. The results of the activity: (a) the implementation of training and assistance in the implementation of guidance and counseling services was able to improve the competence of counseling teachers at MA DDI Wal Irsyad, Pangkep Regency (b) the resolution of problems faced by students based on the methods and strategies of guidance and counseling services that comply with standards which is determined.